Because you have added 7% tax to your own sale price, your net sales is 107% of your sales prior to your tax. As an equation, you would have 1.07x = 6645.16, where x is the sales prior to tax.
To solve this, just divide both sides by 1.07.
x = 6645.16/1.07
x = 6210.43
Your net sales...
The quadratic formula states that for any quadratic equation where ax2 + bx + c = 0, where a is the coefficient of the squared term, b is the coefficient of the term raised to the first power, and c is the constant, the variable will equal [-b+/-√(b2
For the equation that you...
-5a + 4 + 6a = 11 - 30 Given
a + 4 = -19 Simplify (-5a + 6a = a, 11 - 30 = -19)
a + 4 - 4 = -19 - 4 Subtract 4 from each side
a = -23 Simplify (a + 4 - 4 = a, -19 - 4 = - 23)
The sum of cubes states that a3 + b3 = (a + b)(a2 - ab +
Using the sum of cubes, we can factor the numerator:
[(x + y)(x2 - xy + y2)]/(x - y)
Since there are no common factors of then numerator and denominator, the fraction cannot be reduced.
Note that if the numerator...
Substitution method of solving a system of equations requires the replacing of an equivalent value of a variable from one equation for the variable in the other.
y = 2x - 10 Given
4x - 8 = 2x - 10 Substituted the value of y from the 2nd equation for the...
(2-5a-5b10c20)/(162a-6b2c10) Distribute the exponents (multiply to find the power of a power)
(b10c20a6)/(162b2c10*25a5) Negative exponents should be moved to the other part of the fraction
If I understand your question correctly, I believe you are solving (5 - z)/z = 9. If you are, then here are the steps below:
(5 - z)/z = 9 Given
(5 - z)/z * z = 9 * z Multiply both sides by z
5 - z = 9z Simplify
5 - z + z = 9z + z Add...
5x + 3(x - 2) = 4x - (x - 4) Given
5x + 3x - 6 = 4x - x + 4 Distributive property
8x - 6 = 3x + 4 Simplify
8x - 6 + 6 = 3x + 4 + 6 Add 6 to each side
8x = 3x + 10 Simplify
In order to classify conic sections, I recommend that you get all of the variables on the same side of the equal sign (these are already set up in this form), then go through the following flow chart:
1) Are both x and y squared?
If no, it is is a parabola.
If yes, continue to question...
Remember to change the percentage to a decimal by moving the decimal point two places to the left
r = .04
t = 12
I = pre
I = 300 * .04 * 12
I = $144
the interest is 144 dollars
*If this yearly interest and you have 12 months, then you need to change the...
y = (-1/8)x
x - 4y = 4
To use substitution, I am going to replace the y in the second equation with the expression that is equal to y in the first equation.
x - 4(-1/8)x = 4
x + (1/2)x = 4
(3/2)x = 4
If I multiply both sides by 2/3, I have
x = 4(2/3)
x = 8/3
The first step we need to take is to write an equation that represents the number of auto collisions that occur each year. Since the baseline year (1998) involved 26 collisions, 26 will be the constant. Since the decrease is 2.5 per year, the coefficient
on the variable (the slope) will be...
This expression (not equation, since an equation requires an equal sign with something on each side) is a quadratic (second degree polynomial).
The quadratic is in standard form:
ax2 + bx + c
Since you don't see a number written before x2 or x, their coefficients (a & b) are 1
To find the x value of the vertex of a parabola, divide the opposite of the coefficient on the x term by 2 times the coefficient on the y term (-b/2a).
x = 10/2
x = 5
Plug the value that you found for x into the function to find the y value
f(5) = 52 - 10*5 -...
1. Assuming you mean symmetric around the x-axis, the graph of a quadratic is symmetric when b = 0. All quadratics are symmetric around their axis of symmetry.
2. The sign on a will determine if the graph opens up or down. If the sign is positive, the graph opens up. If the sign is negative,...
Since we are looking for the quantity at which supply and demand are equal, we can set quantity equal to itself, then substitute the supply equation for one q and the demand equation for the other.
q = q Reflexive property
-400p + 1500 = 200p...
Since you have already correctly substituted the values of B and C into the equation, we now need to solve using correct order of operations
First, we need to solve the information inside the parenthesis
A = 5 + 3(4 - 2)
A = 5 + 3(2)
Next, we need to multiply
A = 5 + 6
A polynomial requires each term to have all variables with positive integer exponents. Since the last term (8x-2) has a negative exponent on the variable, the function is not a polynomial function.
The restriction on the domain of a rational function (function in which the variable occurs in the denominator), is all values of the variable that make the denominator 0.
As the equation is written, the denominator is y2. If we set the denominator equal to 0 we have:
y2 = 0
3x2 + 2x = 5 Given
3x2 + 2x - 5 = 0 Subtract 5 from each side
(3x + 5)(x - 1) = 0 Factor the left side of the equation
3x + 5 = 0 x - 1 = 0 Set each factor equal to 0
3x = -5 x = 1 Subtract 5 in the first equation, add 1...